2010
DOI: 10.1007/s11030-010-9236-7
|View full text |Cite
|
Sign up to set email alerts
|

Toward a practical and waste-free synthesis of thioureas in water

Abstract: An operationally simple and entirely green protocol for the synthesis of thiourea derivatives by the reaction of carbon disulfide with primary amines in pure water is developed. This reaction is a highly atom-economic process for production of highly pure, hindered thioureas without any catalyst and tedious work-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 23 publications
0
15
1
1
Order By: Relevance
“…Recently, thiourea derivatives have been prepared by condensing primary or secondary amines with carbon disulfide in aqueous media. Prabhu and coworkers, [31] Azizi et al, [32] and Halimehjani et al [33] reported the synthesis of thioureas in aqueous medium under heating, even though carbon disulfide is a volatile liquid having low boiling point (46°C) and was used in excess. Thus, it is important to develop an effective and convergent process for a scale-up preparation of thiourea derivatives at room temperature particularly in green solvent such as water, an important goal in organic synthesis, [34] because water is the most economical and ecofriendly media and most desirable clean solvent for chemical reactions because of its lack of flammable, explosive, mutagenic, and carcinogenic properties, which are some of the economic and environmental concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, thiourea derivatives have been prepared by condensing primary or secondary amines with carbon disulfide in aqueous media. Prabhu and coworkers, [31] Azizi et al, [32] and Halimehjani et al [33] reported the synthesis of thioureas in aqueous medium under heating, even though carbon disulfide is a volatile liquid having low boiling point (46°C) and was used in excess. Thus, it is important to develop an effective and convergent process for a scale-up preparation of thiourea derivatives at room temperature particularly in green solvent such as water, an important goal in organic synthesis, [34] because water is the most economical and ecofriendly media and most desirable clean solvent for chemical reactions because of its lack of flammable, explosive, mutagenic, and carcinogenic properties, which are some of the economic and environmental concerns.…”
Section: Introductionmentioning
confidence: 99%
“…During the course of our study aiming at improving the ecocompatibility of certain organic processes, we have been particularly interested in the development of organic transformations in a purely aqueous system to develop environmentally benign reactions [48–57]. Herein, we wish to report deep eutectic solvent as a novel catalyst and reaction medium for an efficient preparation of 3,4-dihydropyrimidinones under mild reaction conditions with short reaction time and simple work-up.…”
Section: Resultsmentioning
confidence: 99%
“…During the course of our study aimed at improving the ecocompatibility of certain organic processes, we have been particularly interested in the synthesis of dithiocarbamates in water and solvent-free conditions to develop environmentally benign reactions [32][33][34][35][36][37]. Herein, we wish to report an efficient preparation of dithiocarbamate derivatives from the one-pot reaction of amines, carbon disulfide, and unsaturated enones or alkyl halides in water under ultrasound irradiation.…”
Section: Resultsmentioning
confidence: 99%